Smart Spatium: a dynamic collaborative working space for smart campus - Abdullah, Salfarina; Nor Azmi, Nur Farahsyazwani; Anuar, Sazly (Database Technologies and Applications Research Group (DbTA), Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2019)
Smart Spatium is an online dynamic collaborative working space developed for university students as a platform for sharing documents regardless of time and place. It eradicates the difficulty to establish consistent physical meetings by enabling the students to have active collaboration and discussion. Problems concerning work coordination, inability to make document editing, lack of back up platforms, and lack of mechanism that can provide evidence of contribution among team members will all be smartly tackled by this system. Committed to the betterment in active teamwork collaboration regardless of geographical distances, it allows students to commit and actively collaborate in every discussion and best of all; obtain a fair assessment among the team members. It also serves as a centralized platform for storing the folders containing assignments and projects so that the whole application looks more manageable hence can reduce any possible risks. Developed using Rapid Application Development (RAD) methodology, this application is highly suitable for newer generation in virtual learning and online community practice, thus greatly enhances the current education trend and methods.